Soluble Endoglin Serum Level is Higher in Preeclampsia Compared to Molar and Normal Pregnancy - Maya K. Puspitasari; Anita D. Anwar; Firman F. Wirakusumah (Indonesian Socety of Obstetrics and Gynecology, 2014)
Abstract Objective: To analyze th e differences of maternal serum soluble endoglin level in pr eeclampsia, molar pregnan cy, and normal pregnancy, and to analyze th e correlation between maternal serum soluble endoglin level with gestational age. Method: This is a cros s-sectional compara tive analytic study involving 18 preeclamps ia cases, 18 molar pr egnan cies, and 18 normal pregnancies. The sample were obtained from Dr. Hasan Sad ikin hospital and six satellite hospitals from January until Mar ch 2013. The comparison of mean seng se rum level of th e preeclampsia,molar pregnancy, and normal pregnancy gro up was calculated using Kruskal Wallis, and the corr elation we re calculated using Rank Spearman. Result: The mean level of seng se rum in pr eeclamp sia gro up was higher (168.79 ngjml) than in molar pr egnan cy (43.47 ngjml) and normal pregnancy (32.38 ngjml). Ther e is no significant difference of se rum seng level be tween molar and norm al pregnan cy, with p value of 0.393 (p>0.05). There is significant differ ences of seng serum level between pr eeclampsia gro up and molar pr egnancy (p=O.OOO), but no significant differ ences between molar and normal pregnancy, p value=0.393 (p >0.05). Ther e is positive correlati on between seng se rum level of norm al pregnancy with gestational age (rs=0 .647 ; p<0.001). Conclusion: Mat ern al se rum seng level in preeclampsia is higher than th e level of which in molar pre gnan cy and norm al pregnancy. Keywords: molar pregnancy, norm al pr egnancy, pr eeclamp sia, soluble endoglin level